TINJAUAN YURIDIS KUASA MUTLAK DALAM PEMBUATAN AKTA NOTARIS MENURUT PERUNDANG-UNDANGAN DI INDONESIA - EMA EMELIA (PREMISE LAW JURNAL, 2015)
Based on the Instruction of the Internal Affairs Minister No. 14/1982 on the Prohibition to use Irrevocable Power of Attorney as the Transfer on Land Rights on March 6, 1982, there was a prohibited Power of Attorney in which it contained the element which could not be withdrawn by the principal since it is the transfer of land rights. In its development, the Instruction of the Internal Affairs Minister was changed: the Decree of the Agrarian Director General, on behalf of the Internal Affairs Minister No. 594/1492/AGR regulates the use irrevocable power of attorney, not as prohibited irrevocable power attorney as stipulated in sales certificate, sales agreement, and APHT. ). Deviation in irrevocable power of attorney occurred after being revised on March 30, 1982; if it was not revised or rectified, the land would returned to the heir when the seller died, and it would be chaos because the buyer was harmed financially. Therefore, the Circular Letter of the Directorate of Agrarian Affairs No. 594/1492/AGR on March 30, 1982 has been amended by the Government. The legal domicile of the parties concerned in the irrevocable power of attorney can actually be implemented provided that it is united with purchase agreement. Every buy and sell with irrevocable power of attorney is approved by the Supreme Court, and purchase agreement still exists. Keywords: Irrevocable Power of Attorney, Drawing up Deed, Notary/PPAT